Analysis of platelet eluate for the elucidation of sensitization to HLA in kidney transplant candidate - Hugo Mendonça Mundim; Maria Aparecida Caixeta Lins; Eridane Botelho Guzmán; Heline Leal Titan; Patrícia Keiko Saito; Sueli Donizete Borelli (Universidade Estadual de Maringá, 2015)
While a 42-year-old male patient was being prepared for deceased-donor renal transplantation, anti-HLA-A2 antibodies were detected in the serum by enzyme-linked immunosorbent assay (ELISA) method. The patient denied any transfusion history and previous transplant. Crossmatch by complement dependent cytotoxicity (CDC) and CDC with anti-human globulin (CDC-AHG) proved negative with a four-cell panel with positive typing for HLA-A2. Adsorption of antibodies with platelets and analysis of eluate were suggested to elucidate discrepancies in results by ELISA and by CDC-AHG. ELISA showed that adsorbed serum with platelets did not reveal antibodies for HLA-A2 specificity and suggested that they were removed by their specific binding with HLA-A2 antigens on the platelet surface. Eluate analysis by ELISA showed antibodies for HLA-A2 specificity. No antibodies for HLA-A2 specificity in the non-adsorbed serum were detected by CDC-AHG method. Revision of patient's data showed that a previous transfusion had occurred, which may have been the source of HLA sensitization. The suggested method may be a contribution towards the evaluation of sensitivity between CDC-AHG and ELISA methods for characterizing antibodies in the patient's serum.